Role of sublingual immunotherapy and probiotics in clinical improvements of childhood asthma - Mira lrmawati; Anang Endaryanto; Arijanto Harsono (Paediatrica Indonesiana, 2008)
Background Sublingual immunotherapy (SLIT) is an effectivesecondary prevention to improve natural course of asthma. Itsefficacy is limited to allergic asthma caused by inhalant allergen.Recent studies showed that probiotic as immunomodulatordecreases inflammatory process induced by food allergy. No suf-ficient clinical evidence reported about the efficacy of combinationsublingual immunotherapy and probiotics or probiotics only inclinical improvement of childhood asthma.Objective To investigate the role of SLIT and probiotic on clinicalparameters of childhood asthma (FEVl reversibility, medicationscore, and symptom score).Methods A randomized single blind clinical trial was conductedon 6-17 year-old asthmatic children sensitive to food and aero-allergens. Subjects were allocated to Group A receiving SLIT,Group B receiving probiotics and SLIT, Group C receiving probiot-ics only. All parameters were evaluated in week 0 untill4.Results FEVl reversibility improved in all groups. Medicationscore and symptom score was also decreased in all groups. Themost marked decrease of FEVl reversibility and symptom scorewere found in probiotics group. Statistical analysis revealedthat the difference of each parameter between groups were notsignificant.Conclusion Combination of SLIT and probiotics and probiot-ics are only similarly effective to improve clinical symptoms aschildhood asthma. Hence, information about probiotics as im-munomodulator was proved to be an excellent alternative therapyfor childhood asthma has been obtained.